Endothelial Activation, Innate Immune Activation, and Inflammation Are Associated With Postbronchodilator Airflow Limitation and Obstruction Among Adolescents Living With HIV. (1st March 2020) - Attia, Engi F.; Bhatraju, Pavan K.; Triplette, Matthew; Kosamo, Susanna; Maleche-Obimbo, Elizabeth; West, Timothy Eoin; Richardson, Barbra A.; Zifodya, Jerry S.; Eskander, Sherry; Njiru, Christine D.; Warui, Danson; Kicska, Gregory A.; et al.
Abstract : Background: Chronic inflammation, innate immune activation, T-cell imbalance and endothelial activation have been linked with lung diseases. We sought to determine whether markers of these pathophysiologic pathways were associated with spirometry and chest computed tomography (CT) abnormalities among adolescents living with HIV (ALWH). Setting: Coptic Hope Center for Infectious Diseases in Nairobi, Kenya. Methods: We performed a cross-sectional study of ALWH (10–19 years old). Participants underwent chest CT, spirometry, and venipuncture for serum biomarkers. We also collected demographic, anthropometric, T-cell subset, antiretroviral therapy, and exposure data. We compared characteristics and biomarkers by airflow obstruction [postbronchodilator FEV1 /FVC z-score (zFEV1 /FVC) < −1.64]. We used multivariable linear regression to determine associations of log10 -transformed biomarkers and chest CT abnormalities with lower postbronchodilator zFEV1 /FVC (airflow limitation). We performed exploratory principal components analysis on biomarkers, and determined associations of factors with postbronchodilator zFEV1 /FVC and chest CT abnormalities. Results: Of 47 participants with acceptable quality spirometry, 21 (45%) were female, median age was 13 years and 96% had perinatally-acquired HIV. Median CD4 was 672 cells/µL. Overall, 28% had airflow obstruction and 78% had a chest CT abnormality; airflow obstruction was associated with mosaic attenuation ( P = 0.001). Higher endothelial activation (sVCAM-1, sICAM-1), inflammation and innate immune activation (serum amyloid-A, sTREM-1, sCD163), and T-cell imbalance (lower CD4/CD8) markers were associated with airflow limitation. Factors comprising endothelial and innate immune activation were associated with airflow limitation. Conclusions: Endothelial activation, innate immune activation, T-cell imbalance, and chronic inflammation are associated with airflow limitation and obstruction, providing insights into chronic lung disease pathophysiology among ALWH.